2023
DOI: 10.1021/jacs.2c12648
|View full text |Cite
|
Sign up to set email alerts
|

Diastereodivergent Desymmetric Annulation to Access Spirooxindoles: Chemical Probes for Mitosis

Abstract: Spirooxindoles have emerged as promising architectures for engineering biologically active compounds. The diastereodivergent construction of unique scaffolds of this type with full control of continuous chiral centers including an all-carbon quaternary stereogenic center is yet to be developed. Here, we report an unprecedented diastereodivergent desymmetric [3 + 3] annulation of oxabicyclic alkenes with enals enabled by N-heterocyclic carbene (NHC)/Rh cooperative catalysis, leading to a series of enantiomerica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 71 publications
0
15
0
Order By: Relevance
“…It would be more appealing if less active but readily available simple alkenes or alkynes could undergo Csp3–Csp3 coupling reactions for stereodivergent synthesis. Another challenge is that while iridium- and palladium-involved synergistic catalyses have proven to be successful in stereodivergent synthesis, expanding the scope to other transition-metal-related synergistic catalysis is attractive. Additionally, despite the achievements in constructing vicinal stereocenters, the stereodivergent preparation of 1, n -remote multistereocenters with a single transformation is still limited. Finally, gaining mechanistic insights into the origins of the stereochemistry, especially understanding how the two catalysts cooperate with each other in the synergistic system, is highly desirable. However, due to the complexity of the system, theoretical studies in this field are still in their infancy. …”
Section: Summary and Outlookmentioning
confidence: 99%
“…It would be more appealing if less active but readily available simple alkenes or alkynes could undergo Csp3–Csp3 coupling reactions for stereodivergent synthesis. Another challenge is that while iridium- and palladium-involved synergistic catalyses have proven to be successful in stereodivergent synthesis, expanding the scope to other transition-metal-related synergistic catalysis is attractive. Additionally, despite the achievements in constructing vicinal stereocenters, the stereodivergent preparation of 1, n -remote multistereocenters with a single transformation is still limited. Finally, gaining mechanistic insights into the origins of the stereochemistry, especially understanding how the two catalysts cooperate with each other in the synergistic system, is highly desirable. However, due to the complexity of the system, theoretical studies in this field are still in their infancy. …”
Section: Summary and Outlookmentioning
confidence: 99%
“…The same group also disclosed the feasibility of merging NHC catalysis with Rh-catalyzed asymmetric ring-opening (ARO) reactions (Scheme ). Transition-metal-catalyzed ARO reactions proceeded through the generation of an electrophilic species (for example, Rh- 62 ) via desymmetric oxidative addition of low valent transition-metal into a bridge-head C–O bond. Gong and co-workers demonstrated that the key intermediate Rh- 62 could be trapped by an NHC-homoenolate 63 , and the two thus-generated stereocenters in this coupling step were almost fully and independently controlled by Rh­(I)/ L13 and NHC 50 , respectively.…”
Section: Dual Organo/metal Catalysismentioning
confidence: 99%
“…It is worth pointing out that four stereoisomers of the spirooxindole products were obtaineded with high diastereoselectivity and enantioselectivity by only switching the enantiomeric pairs of the two catalysts (Scheme 57). [96] Control experiments suggested that the competing ligation between the NHC catalyst and the rhodium center probably occurred to somewhat quench the catalytic activity of the rhodium complex and NHC. In addition, biological investigations revealed this novel class of spirooxindoles inhibiting mitotic progression against HeLa cells.…”
Section: Nhc‐catalyzed Cycloadditions For the Construction Of Spiroox...mentioning
confidence: 99%